Barriers to the Implementation of Industry 4.0: The Perspective of Manufacturing SMEs - Anna KWIOTKOWSKA (Communications of International Proceedings, 2021)
The fourth industrial revolution is perceived by manufacturing companies as an important factor in maintaining competitiveness, while at the same time presenting them with significant technological, organizational and managerial challenges. The purpose of this paper is to explore how top executives of manufacturing SMEs interpret the concept of Industry 4.0, and especially what major barriers they perceive in implementing Industry 4.0. The paper uses a qualitative case study design involving 34 semi-structured interviews with leading members of firms, including chief digital officers and chief executive officers. Company websites and annual reports were also examined to increase the reliability and validity of the results. The paper identifies the six main factors define Industry 4.0 and the primary barriers to the introduction of new digital technologies to Industry 4.0, divided into two groups relating to non-technical challenges and those related to technology and process integration.
Keywords: Industry 4.0; barriers; manufacturing SMEs.